Microbial activity and plant nutrients transformation as influenced by herbicides application in soil - Panda, N; Raha, P; Kumar, Anjani (ORYZA-An International Journal of Rice, 2018)
Several environmental factors affect the soil ecology. Use of herbicides in rice has often resulted in contamination of the soil ecosystem, by direct or indirect action, after short, average or long period of time. To test this hypothesis, a laboratory study was conducted to assess the effect of herbicide glyphosate, paraquat and pendimethalin on reduction of plant nutrients (Fe, Mn), soil microbial biomass carbon and soil dehydrogenase activity under the submerged soil condition. Glyphosate at field application dose (0.90 mg g-1) and double field application dose (1.80 mg g-1) inhibited in reduction of Fe and Mn from 5.18 to 14.35% and stimulated the soil dehydrogenase activity from 11.64 to 43.12 %. However, both inhibition and stimulation effect on reduction in plant nutrient (Fe, Mn), soil microbial biomass carbon (MBC) and soil dehydrogenase activity was resulted from application of herbicides paraquat and pendimethalin at their field (0.45 mg g-1) and double field application dose (0.90 mg g-1).